Determining in‐patient diabetes treatment satisfaction in the UK—the DIPSat study. Issue 6 (6th March 2013) - Rutter, C. L.; Jones, C.; Dhatariya, K. K.; James, J.; Irvine, L.; Wilson, E. C. F.; Singh, H.; Walden, E.; Holland, R.; Harvey, I.; Bradley, C.; Sampson, M. J.
Abstract Aims To measure in‐patient diabetes treatment satisfaction and its relationship to in‐patient diabetes care. Methods In a cross‐sectional study, diabetes in‐patient specialist nurses at 58 UK hospitals asked insulin‐treated in‐patients with diabetes to complete the recently updated Diabetes Treatment Satisfaction Questionnaire for In‐patients and a general questionnaire; 1319 in‐patients completed these questionnaires. Results Satisfaction with the general diabetes treatment items in the Diabetes Treatment Satisfaction Questionnaire for In‐patients was high, but there were high levels of extreme dissatisfaction with meal choices, meal quality and lack of similarity of hospital meals to normal domestic choices—23% would never or rarely have made similar meal choices at home. Hyperglycaemia or hypoglycaemia was reported for much of the in‐patient stay (20% and 7%, respectively) and 26% reported at least one severe hypoglycaemic episode; these groups had lower satisfaction with the timing of medication in relation to meals (P < 0.003). More frequent in‐patient hyperglycaemia or hypoglycaemia were associated with significantly poorer overall satisfaction scores and negative well‐being scores (both P < 0.0001). Previous experience of a multiple daily insulin injection regimen was associated with more dissatisfaction than other regimens (P < 0.01). Multiple regression models explained 36% of variability in overall treatment satisfaction, with most (22.4%) accounted for by satisfaction with time spent with a diabetes in‐patient specialist nurse (P < 0.0001). Self‐administration of insulin was independently associated with higher treatment satisfaction (P < 0.006) in this model. Conclusions The DIPSat programme describes the complex relationships between diabetes in‐patient treatment satisfaction and in‐patient diabetes care.